2008
DOI: 10.5603/arm.27891
|View full text |Cite
|
Sign up to set email alerts
|

Protein C System in Patients with Idiopathic Pulmonary Fibrosis—Preliminary Report

Abstract: Introduction: The natural anticoagulant—activated protein C system plays an important role in the pathogenesis of idiopathic pulmonary fibrosis. The purpose of this study was to evaluate the concentration of protein C (PC), protein S (PS), thrombomodulin (TM), selectin E (sSelE), and thrombin–antithrombin complex (TAT) in patients with idiopathic pulmonary fibrosis (IPF). Material and methods: Study grup consisted of 11 patients aged 51.5 ± 8.62 years with idiopathic pulmonary fibrosis and 20 healthy adults as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Protein S can be found in plasma in a free form or complexed to C4BP (C4b-binding protein) [ 79 , 80 ]. In a study on 33 IPF patients and 44 controls, no significant differences were observed in the circulating levels of free and total protein S in IPF patients compared with healthy individuals [ 81 ], while in another study, lower plasma concentrations of protein S were detected in a small cohort of 11 patients affected by IPF if compared to 20 healthy controls [ 82 ]. More recently, it was reported that 3,5,3′-triiodothyronine (T3) administration in a mice model of pulmonary fibrosis improved alveolar regeneration, in a process involving protein S-TAM signaling [ 83 ].…”
Section: Gas6/tam In Lung Fibrosismentioning
confidence: 99%
“…Protein S can be found in plasma in a free form or complexed to C4BP (C4b-binding protein) [ 79 , 80 ]. In a study on 33 IPF patients and 44 controls, no significant differences were observed in the circulating levels of free and total protein S in IPF patients compared with healthy individuals [ 81 ], while in another study, lower plasma concentrations of protein S were detected in a small cohort of 11 patients affected by IPF if compared to 20 healthy controls [ 82 ]. More recently, it was reported that 3,5,3′-triiodothyronine (T3) administration in a mice model of pulmonary fibrosis improved alveolar regeneration, in a process involving protein S-TAM signaling [ 83 ].…”
Section: Gas6/tam In Lung Fibrosismentioning
confidence: 99%